PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN KOSMETIK PIXY DI MATAHARI MEGA MALL KOTA BATAM - Elok Pitaloka Putri; Syaifullah (LPPM Universitas Putera Batam, 2022)
The purpose of this study was to determine whether consumer satisfaction with Pixy cosmetics at Matahari Mega Mall Batam City is influenced by service quality, product, and brand image. The research was conducted using quantitative techniques. 283 people who shop at Matahari Mega Mall Batam City are the population that is being exploited. 166 consumers became the research sample, which were selected using a simple random sampling method. Questionnaires were used as a data collection technique. By using SPSS 25 software, data analysis techniques include descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis testing. Consumer satisfaction is influenced by 67.7% by the coefficient of determination (R2) which comes from the variables of service quality, product quality, and brand image. Based on the results of multiple linear regression, service quality has an effect of 0.113 or 11.3% on consumer satisfaction (Y), product quality (X2) has an effect of 0.288 or 28.8% on consumer satisfaction (Y) and image (X3) has an effect of 0.216 or 21.6% of consumer satisfaction (Y). Based on the results of the t test, service quality has a partially significant effect on consumer satisfaction, product quality has a partially significant effect on consumer satisfaction, brand image has a partially significant effect on customer satisfaction, and the f test results for service quality, product quality and brand image have a significant simultaneous effect. on consumer satisfaction.